Community Composting A step towards clean India movement - Mukherjee, Anirban; Chakraborty, Debasish; Shubha, Kumari (Indian Farming, 2017)
Sustainable waste management through composting is an important step towards bringing cleanliness and sanitation in the society. But for this, the community (people) have to come together and take active participation in reaching this goal.